The revolution in Constantinople and Turkey a diary - Ramsay, William Mitchell; Ramsay, W. M.; Ramsay (Hodder and Stoughton, 1909)
Ramsay published this travel diary very shortly after the Young Turk Revolution. Ramsay, sympathetic to the Young Turks, wished to convey the general feelings and impressions of the people in the Ottoman Empire at the time he traveled through it, thus rumors, mistaken impressions, and incomplete information are not edited out or corrected. However, Ramsay does provide some notes in brackets when he knows of an incorrect report. Ramsay is seemingly in touch with the political situation; he makes a conscientious effort to note incorrect impressions from his informants. Generally it is not clear if he got his information from foreigners living in Turkey, from well-placed Turkish intellectuals, from newspapers, or elsewhere. Ramsay's attitude toward the people of the region is generally sympathetic. He concludes the book by complaining about British red tape in the Foreign Office. Ramsay's wife was a photographer and provided almost all the photographs in the book along with a few chapters related to Turkish women.
Ramsay published this travel diary very shortly after the Young Turk Revolution. Ramsay, sympathetic to the Young Turks, wished to convey the general feelings and impressions of the people in the Ottoman Empire at the time he traveled through it, thus rumors, mistaken impressions, and incomplete information are not edited out or corrected. However, Ramsay does provide some notes in brackets when he knows of an incorrect report. Ramsay is seemingly in touch with the political situation; he makes a conscientious effort to note incorrect impressions from his informants. Generally it is not clear if he got his information from foreigners living in Turkey, from well-placed Turkish intellectuals, from newspapers, or elsewhere. Ramsay's attitude toward the people of the region is generally sympathetic. He concludes the book by complaining about British red tape in the Foreign Office. Ramsay's wife was a photographer and provided almost all the photographs in the book along with a few chapters related to Turkish women.
Keywords: Turkey / Politics and government / 1878-1909; Turkey / History / Revolution, 1908; Turkey / Description and travel.